Religious Diversity and Covenantal Pluralism in the Philippines - Serrano Cornelio, Jayeel (The review of faith & international affairs, 2020)
In spite of the enduring dominance of Catholicism in Philippine society, religious diversity increasingly characterizes its social and political life. This diversity is predominantly Christian, given the rise of evangelical, independent, and even nontrinitarian churches around the country. Is covenantal pluralism possible? This article answers this question by focusing on what Filipino Christians believe about religion and pluralism. It draws on the 2018 ISSP Religion module to analyze the relationship between denominational affiliation and attitudes about religion and coexistence. Our argument is that Filipino Christians, as a whole, are divided on whether they can live amicably with one another. Two observations substantiate this point. First, Catholics believe that religion brings conflict and that religious people tend to be intolerant more than do members of other churches. Second, in comparison to Catholics, Protestants/Evangelicals and Nontrinitarians are more inclined to believe that practicing religion fosters friendships. Taken together, these dispositions present challenges and opportunities for covenantal pluralism in the country. This article ends by reflecting on covenantal pluralism as a relational call in a society where emerging religious minorities are increasingly influential and competitive.